Beethoven House in Heiligenstadt near Vienna - Perger, Sigmund Ferdinand von, 1778-1841 (artist):::Creator:::::::::::: (2020)
Watercolor etching of Beethoven in the Pfarrplatz in Heiligenstadt near the house where he lived (Schlöglisches Haus, 66 Am Platz).